Contact hypersensitivity test and specificity to mercury (Hg) in Wistar rat - Yustina Andwi Ari Sumiwl, Yustina Andwi Ari Sumiwl (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
Mercury is one of the potent allergens which can induce contact hypersensitivity. This substance however, is commonly used for cosmetics and medical purposes. The exact mechanisms underlying the mercury-induced hypersensitivity remain unclear. Studies on mercury contact hypersensitivity in human were hampered due to ethical reason. This investigation was, therefore, aimed at studying hypersensitivity reactions In animal model. Thirty five female Wistar rats, aged three months were divided into three groups of treated animals and two groups of controls. The treated groups were sensitized with 2,5%, 5%, and 10% HgCl2 In petrolatum for 10 days. At day 14, animals were challenged with 5% HgCl2 in 97% ethanol. Contact hypersensitivity was assessed by measuring the ear swelling before and after ear challenge. Specificity test was carried out by challenging the sensitized animals with K2Cr207. The results showed that the, peak levels of ear swelling could be achieved by applying 10% HgCl2 as compared to other groups of animals. Chromium (K2Cr207) ear challenge following 10% HgC12 sensitization failed to induce ear swelling. It can be concluded that the mercury hypersensitivity reaction in this animal model is antigen-specific.Key words: allergy - contact hypersensitivity-mercury - DTH reaction - Wistar rats